Harvesting period of jabuticaba fruits var. ‘Pingo de Mel’ in relation to the physicochemical characterization evaluated during their development - Flávio Alves da Silva, Lismaíra Gonçalves Caixeta Garcia; Asquieri, Eduardo Ramirez; Vilas Boas, Eduardo Valério de Barros; Silva, Clarissa Damiani, Monik Marielly Moreira (Emirates Journal of Food and Agriculture, 2018)
The objective was to physically and chemically characterize jabuticaba fruits var. ‘Pingo de Mel’ during their development. Some fruits were harvested ten days after flowering (DAF) and harvesting was continued at four day intervals until the fruits were completely ripe (34 days). It was shown that the values for the diameter, mass, soluble solids and anthocyanins increased up to 30 DAF, whereas the soluble pectin content and ratio (relationship between soluble solids content and titratable acidity) increased up to 34 DAF. The respiratory rate showed the opposite behavior, reducing up to 30 DAF, and the values for firmness and chlorophyll reduced up to 34 DAF. The pH and ratio reduced up to 18 DAF with a subsequent increase up to 34 DAF, whereas the acidity showed the opposite behavior. In order to obtain high quality fruits with respect to ripeness it is important to consider the soluble solids and anthocyanin contents, which the present study showed to be indicators of the best moment for harvesting, that is, 30 DAF.